APPLICATION OF BIG BOOK MEDIA ON PROCEDURE TEXT WRITING SKILLS OF CLASS XI-3 STUDENTS OF SMAN 1 SEKARAN - Mualifah, Siti; Selirowangi, Nisaul Barokati; Lestari, Laila Tri (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2024)
This research is a mixed research which aims to improve the writing skills of class XI-3 students at SMAN 1 Sekaran. Mixed methods is an approach that combines or connects quantitative and qualitative in one study so that more comprehensive, valid and objective data is obtained. The source of research data was obtained from student worksheets. The technique used is a data recording technique. Data is collected in table form and then described. The research results obtained were that the application of Big Book media to procedural text writing skills material was categorized as very good with a percentage of 95.32. This data is obtained from teacher activities and student activities. Judging from the activities of teachers in the very good category, the percentage is 96.43%.. Based on student activity, it is categorized as very good with a percentage of 94.21%. The application of Big Book media in learning procedural texts in terms of student learning completeness is categorized as very good with a percentage of 94.95%. The application of the Big Book media in procedural text writing skills material was reviewed by responses from students in the very good category with a percentage of 88.195% or effective for application in class XI-3 SMAN 1 Sekaran.